Developmental Potential and Efficiency of Black Bengal Goat Embryo Production by using Intracytoplasmic Sperm Injection and In Vitro Fertilization - Bori, Joygeswar; Boruah, Jyoti Lakshmi Hati; Phukan, Amlan Jyoti; Chandra Sarkhel, Bikash; Kumar, Dharmendra; Morang, Munmi (The Indian Journal of Animal Reproduction, 2025)
This study aimed to optimize an intracytoplasmic sperm injection (ICSI) for in vitro embryo production in black bengal  goats and compare its efficiency with in vitro fertilization (IVF). A total of 744 oocytes were retrieved from 269 slaughter house-derived ovaries, with an average recovery rate of 2.76 oocytes per ovary. Only grade I and II oocytes (n = 534) were  selected for maturation, of which 376 (70.41%) reached metaphase II. For ICSI, epididymal sperm with broken tails were  microinjected into mature oocytes using a 5 µm micropipette, yielding a high survival rate (83.21%) and a low degener ation rate (17.78%, p < 0.05). Chemical activation using ionomycin, cycloheximide (CHX), and 6-DMAP resulted in a  74.44% cleavage rate (p
Keywords: Epididymal Sperm injection; Goat; Embryo Development; In vitro; Intracytoplasmic Sperm injection (ICSI); In Vitro Fertilization (IVF)